1975
DOI: 10.2134/agronj1975.00021962006700050016x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics of Soil Mixtures Used for Golf Green Construction1

Abstract: Large amounts of money are invested each year in the preparation of mixtures for the construction of golf greens and athletic fields. Few efforts have been made to completely characterize the physical properties of the resulting greens. Therefore, a greenhouse experiment was conducted to determine the physical characteristics of a range of sand and soil mixtures for golf green construction. Treatment variables included the amount and texture of soil used in the mixture and the presence or absence of a sand lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Although trampling did not significantly affect total porosity or bulk density (Table 3), intensive foot traffic and wear tore the cells of turfgrasses, and apparently closed macropores of thatchy soil surface. The results of soil volume and mass relationships indicate that the putting green mixture of sand and peat restricted soil compaction, thus agreeing with Swartz and Kardos (1963) or Brown and Duble (1975). Soil compaction was, although slightly, recorded by increased soil mechanical impedance (Fig.…”
Section: Soil Physical Conditionsupporting
confidence: 67%
“…Although trampling did not significantly affect total porosity or bulk density (Table 3), intensive foot traffic and wear tore the cells of turfgrasses, and apparently closed macropores of thatchy soil surface. The results of soil volume and mass relationships indicate that the putting green mixture of sand and peat restricted soil compaction, thus agreeing with Swartz and Kardos (1963) or Brown and Duble (1975). Soil compaction was, although slightly, recorded by increased soil mechanical impedance (Fig.…”
Section: Soil Physical Conditionsupporting
confidence: 67%
“…Brown & Dubie (1975) also showed that a range of particle sizes gave good results for golf green construction. Therefore other physical properties should be considered in the selection of a mixture of aggregate sizes to meet the needs of environmental conditions.…”
Section: Discussionmentioning
confidence: 90%
“…AlthQugh a size range between 0.5 and 1.0 mm appears tQ be best, gQQd roQt penetratiQn was 'Obtained over a wide range 'Of particle sizes. Brown & Dubie (1975) alsQ showed that a range 'Of particle sizes gave good results fQr gQlf green cQnstructiQn.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in percolation rate of the finest aggregate « 0.5 mm), even without amendment or plant growth, would suggest that percolation would be borderline based on observations of local greens which have been constructed of fine wind-blown sand. The effect of cotula growth on percolation rate is not known, but with turfgrass (Brown & DubIe 1975) percolation was markedly reduced and the minimum rate of 14 cm/hour preferred by Radko (1974) could be reached. Conversely the two coarser layers were lacking in moisture retention.…”
Section: Discussionmentioning
confidence: 99%